The influence of Indigenous status on the issue of police cautions - Weatherburn, Donald James (Journal of criminology, 2023)
Over the last 20 years, a body of research has emerged in the United States (US) revealing that the country?s sentencing courts to treat young male African American (and Hispanic) offenders more harshly than white offenders, even after adjusting for relevant legal and contextual factors. Similar research in Australia has generally found that the effect of Indigenous status on adult bail/sentencing outcomes is either non-significant, or significant, but very small. The aim of this study is to explore the impact of race, age, and gender on police decisions to prosecute rather than caution to a juvenile offender. We employ a multilevel model with random intercepts to explore the impact of race, age, and gender on police decisions to prosecute rather than caution to a juvenile offender. The first level controls for offender/offence factors a police officer may legally consider when deciding whether or not to caution a young offender. The second level controls for the police patrol to which the police officer is attached. After adjusting for the effects of legally relevant factors, we find Indigenous juvenile offenders (regardless of sex) are more likely to be prosecuted than cautioned, compared with their non-Indigenous counterparts. There is also wide variation across local area commands in willingness to caution juvenile offenders. We conclude that further research is needed to obtain a better understanding of the factors responsible for racial disparity in the use of police cautions.